Can vertical farms outgrow their cost? - An analysis of the competitive strength of vertical - Dahlberg, Adam; Lindén, Adam (My University, 2019)
Globalisation and urbanisation are creating sustainability challenges in the global food system that require new methods for food production. Over 80 % of fruits and greens consumed in Sweden are imported, accompanied with climate damaging side effects like excess packaging, transportation, storing and cooling. With the introduction of vertical farming (VF), urban agriculture is undergoing a transition towards drastically higher crop yields and increased quality control in order to deliver more sustainable, resilient and safe food production. VF could become a viable alternative to imported greens in Sweden, benefitting both local producers and consumers. The thesis aims to explore the financial, logistical and environmental prerequisites for successfully implementing VF in Sweden, contributing to a more sustainable agricultural industry. A literature review of business models, industry analysis, sustainability and customer acceptance are used to create a theoretical framework. Data about vertical farming actors is gathered through interviews using a qualitative research method, and two field studies were conducted in Tokyo, Japan. The interview data was analysed with the help of the theories and tools presented in the theoretical framework. Several environmental and social benefits, concerning both the producer and other stakeholders, were identified and point towards more sustainable agricultural practises. Overcoming the economic challenges requires technological improvements to create entry barriers and mitigate bargaining power, development in automatization, and reaching economies of scale. The competitive edge over conventional farming methods comes from the ability to produce crops of consistent quality and quantity year-round in close connection to the consumers. The study indicates that Sweden is a promising country with the right prerequisites to adopt vertical farming. The effect of implementing vertical farming will be a step forward in reducing the environmental impact of agricultural practises while enabling a consistent production of high-quality crops in urban environments.
Keywords: Transport; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Övrig industriell teknik och ekonomi; Transport; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Other industrial engineering and economics